Planning and designing livable recreational open spaces in developing countries. Insights from Souk Ahras City, Algeria - Hafsi, Fatma Zohra (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Creating livable recreational public open spaces is essential for urban quality of life and well-being. In the Algerian context, the topic of public open spaces has been extensively investigated. However, little research has examined how spatial and physical attributes of recreational open spaces influence their use and perceptions by residents. This study investigated the role of urban planning and urban design in shaping livable recreational open spaces in Souk Ahras City, Algeria. The study used a mixed-methods approach: spatial analysis was used to map five typologies, while a survey among 426 residents was used to assess the residents’ satisfaction, use, and perception of recreational open spaces. Although several recreational spaces have been, their availability was insufficient. In addition, satisfaction levels with the spatial and physical attributes of recreational open spaces were mainly average to low. Moreover, satisfaction was positively correlated to use frequency, duration, and favorable perception, highlighting the importance of the design quality of those spaces. However, satisfaction did not predict activities undertaken, underscoring the need for considering more than just the physical aspect when new recreational open spaces are proposed. Recommendations include increasing provision and improving spatial and physical attributes. The findings provide empirical insight to guide context-specific interventions for improving developing cities’ recreational open spaces. Further research should examine interactions between space, culture, and policy across multiple developing cities.